The development of future time expressions in Late Modern English: redistribution of forms or change in discourse? - Nesselhauf, Nadja (English language and linguistics, 2010)
This article provides the first comprehensive analysis of the development of the future time expressions will, ’ll, shall, be going to, progressive with future time reference, and be to in the course of the late modern period. The article focuses on possible reasons for the considerable changes that have taken place in the past few centuries. To what degree can the changes be described as certain forms having been (partially) replaced by others? To what degree have general or register-specific changes in discourse affected the use of future time expressions? These questions are investigated on the basis of the British part of ARCHER (A Representative Corpus of Historical English Registers).The analysis reveals that it is a complex interaction of both types of processes that is responsible for the recent evolution of future time expressions. Redistribution processes turn out to be highly complex in themselves, going far beyond the frequently described replacement of shall by will and probably proceeding in chains. With respect to discourse change, one result is an unexpected overall decrease in the tendency of writers (and speakers) to refer to their own plans, intentions, etc. Partly responsible for this development is a discourse change in science writing, where the author has increasingly disappeared from the text, so that text structure is much less frequently expressed in terms of the author's intention. A further register-specific discourse change that the investigation brings to light is a development in diaries from an earlier restriction to reporting past events to the expression of more personal views, including hopes and fears for the future.